Parent and child dietary changes in a 6-month mobile-delivered weight loss intervention with tailored messaging for parents - Nezami, Brooke T.; Wasser, Heather M.; Tate, Deborah F. (Frontiers in Public Health, 2022)
Objective: To examine changes in parent and child dietary intake, associations between program adherence and parent dietary changes, and the association between parent and child dietary changes in a mobile-delivered weight loss intervention for parents with personalized messaging. Methods: Adults with overweight or obesity and who had a child aged 2-12 in the home were recruited for a randomized controlled trial comparing two types of dietary monitoring: calorie monitoring (Standard, n=37) or "red" food monitoring (Simplified, n=35). Parents received an intervention delivered via a smartphone application with lessons, text messages, and weekly personalized feedback, and self-monitoring of diet, activity, and weight. To measure associations between parent and child dietary changes, two 24-hour recalls for parents and children at baseline and 6 months measured average daily calories, percent of calories from fat, vegetables, fruit, protein, dairy, whole grains, refined grains, added sugars, percent of calories from added sugars, and total Healthy Eating Index-2015 score. Results: Higher parent engagement was associated with lower parent percent of calories from fat, and greater days meeting the dietary goal was associated with lower parent daily calories and refined grains. Adjusting for child age, number of children in the home, parent baseline BMI, and treatment group, there were significant positive associations between parent and child daily calories, whole grains, and refined grains. Parent-child dietary associations were not moderated by treatment group. Conclusions: These results suggest that parent dietary changes in an adult weight loss program may indirectly influence child diet.